Protective factors for posttraumatic stress disorder among healthcare workers during the covid-19 pandemic - Shirzad, Boshra; Kianimoghadam, Amir Sam; Farahani Alavi, Samira; Bakhtiari, Maryam (Researcher Bulletin of Medical Sciences, 2024)
Background and Objective: Healthcare Workers (HCWs) are among at-risk population for trauma exposure and Posttraumatic Stress Disorder (PTSD) development, especially during the Covid-19 pandemic. The aim of the present study was to investigate three different variables, namely coping dimensions, resilience, and spiritual well-being, as protective factors for PTSD development among HCWs during the Covid-19 pandemic. Materials and Methods: In the present study, 300 HCWs were recruited using convenience sampling method. The participants completed a battery of measures, including Posttraumatic Stress Disorder Checklist, Life Paths Measurement Packet Coping Scale, Brief Resilience Scale, and Spiritual Well-being Questionnaire. Results: The Pearson correlation coefficient results revealed that there was a significant positive correlation between PTSD and communication with others (P<0.05, r=0.135), and between other components of spiritual well-being, i.e, communication with self, communication with God, communication with others, and communication with nature. Simultaneous regression analysis results revealed that coping dimensions, resilience, and spiritual well-being explained 4% of the variance in PTSD among the study sample. Also, the results showed that there was a significant positive correlation between communication with others and PTSD (P=0.001, β=0.211, B=0.290), while there was a significant negative relationship between communication with nature and PTSD (P=0.006, β=0.217, B=0.233). Conclusions: These results suggest that spiritual well-being, coping strategies, and resilience, might play a protective role (although minimal) in the development of PTSD among HCWs. Further research is needed in order to make a conclusive decision about using these factors as therapeutic factors to mitigate the onset of PTSD among HCWs during the Covid-19 pandemic.